DEVELOPMENT OF THE CREATIVITY POTENTIAL OF THE STUDENT’S PERSONALITY - van Gejeka, Nataļja; Pakrastiņš, Leonīds; Ignatjeva, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The purpose of this article is to show the increasing of the individual creativity potential on the base of the students’ integrative collaboration during the acquisition of the Building Constructions subject in professional university. The article deals with the issue of demand for highly-qualified, skillful and competitive specialists able to work in interdisciplinary team and organize collective work. Quantitative data analysis method was applied for analyzing the change in students’ creative abilities after the pedagogical experiment – adapted tests of creative abilities, which were developed by E. Torrens. Increase of the students’ creativity in the experimental class was deducted from the obtained data.